Assessment on Improvement of Early Detection Systems in Electrical Rooms of High-Tech Facilities. (2018) - Chen, Yu-Jen; Shu, Chi-Min; Ho, San-Ping; Ho, Hsin-Hsiu; Chang, Hue-Pei
Abstract: Past air sampling detection (ASD) systems had no definitive positioning; most allocation of sampling points was based on experience. This research discovered that sampling points inside the electrical rooms were significantly affected by the ambient airflow, causing the detection system to have difficulties in fire detection. Fire dynamics simulator (FDS) was used to simulate very early smoke detection apparatus (VESDA) effectiveness within the protection area of an electrical room. Results showed that ASD sampling points in electrical rooms should be placed above high-voltage transformers and capacitors, while rearranging the high risk machines together to avoid long detection pipelines, which increases the transportation time of the gas, thus hindering early detection by the ASD system. Field tests using a smoke detector tester yielded transportation times of 33 s, which was in very good agreement with the simulated results of 35 s by ASPIRE, showing the accuracy of using software to simulate transportation times. Therefore, this research combined FDS with the transportation times of different pipeline designs to conduct performance assessment of VESDA. After appropriate rearrangement of machines, VESDA detection times dropped from 106.0–171.0 s during the original setup to 21.0–31.7 s, assuring the facility to have more time for emergency response. However, it was noticed that FDS software did not have the estimation tool for VESDA transportation times; therefore software such as ASPIRE should be used to calculate the gas transportation times inside the detection pipelines, and then compiled with FDS results to avoid underestimation of actuation times.